2021
DOI: 10.3390/ma14030596
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Lipid Carriers Engineered as Topical Delivery of Etodolac: Optimization and Cytotoxicity Studies

Abstract: Etodolac (ETD), a nonsteroidal anti-inflammatory drug, exhibits antinflammatory, analgesic, and antipyretic activity. The main type of ETD administration is oral route, which is associated with significant systemic side effects. Nanostructured lipid carriers (NLC), a modern lipid formulation, are non-toxic, biocompatible, can improve the solubility and stability of drugs. Nanostructured lipid carriers (NLC) containing etodolac were prepared by a melt-emulsification and ultrasonication technique. Full factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…It is found that the EE of tea seed oil in the NLC-C particles is 96.26 ± 2.26%. Lipophilic drugs result in high EE of NLC because they are highly associated with lipid phase [ 62 ]. The result of this study that shows high quantitative encapsulation of tea seed oil is due to the high lipophilicity of the oil in combination with its low aqueous solubility.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the EE of tea seed oil in the NLC-C particles is 96.26 ± 2.26%. Lipophilic drugs result in high EE of NLC because they are highly associated with lipid phase [ 62 ]. The result of this study that shows high quantitative encapsulation of tea seed oil is due to the high lipophilicity of the oil in combination with its low aqueous solubility.…”
Section: Resultsmentioning
confidence: 99%
“…LORA-NLCs were prepared by using hot melt emulsification combined with high-speed stirring and ultrasonication methods (Czajkowska-Kośnik et al, 2021 ), where LORA (10 mg) was combined with solid lipid Compitrol 888 ATO ® and liquid lipids whether (Labrasol ® or Labrafil ® ) a clear and homogeneous oil phase was produced when heated to 85 °C with moderate mixing (Kar et al, 2017 ). The overall amount of solid and liquid lipid inside the blend was 1% (w/v).…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of NLCS were performed by using emulsification-sonication methods [10][11][12][13]. Oleic acid and compritol, oleic acid and gelucire derivatives (Gelucire 48/16 and Gelucire 43/01 pellets) were used as the lipid phase.…”
Section: Preparation Of Nlcsmentioning
confidence: 99%